UNCLOS 1982 AND THE LAW ENFORCEMENT AGAINST ILLEGAL FISHING IN INDONESIA: JUDGES’ DIVERGING PERSPECTIVES - Agustina Merdekawati; Taufiq Adiyanto; Irkham Afnan Trisandi Hasibuan (Mimbar Hukum, 2021)
Abstract Indonesia has not been able to come up with an effective punishment enforcement to deal with illegal, unreported, unregulated fishing (IUUF) in its Exclusive Economic Zone (EEZ), partly due to certain legal limitations put forward in United Nations Convention on The Law of the Sea 1982 (UNCLOS 1982) regarding the permissible punishment. There are two perspectives of Indonesian judges regarding the imposition of penalties towards IUUF offenders in Indonesia’s EEZ. They agree to impose fines but differ on whether to add substitutive confinement. This study aims to understand the diverging views of judges regarding the implementation of UNCLOS 1982 provisions and to provide recommendations to optimize the law enforcement of fisheries regulations. This study is a normative legal research, which utilizes secondary data. This study concludes that the diverging view is correlated to the judges’ view on the adoption of international laws into national laws and that it is imperative for the Government to choose and optimize one legal policy to achieve an effective law enforcement regime. Intisari Indonesia mengalami kendala dalam menerapkan penegakan hukuman terhadap pelaku illegal, unreported, unregulated fishing (IUUF) di Zona Ekonomi Eksklusif (ZEE). Terdapat dua perspektif hakim-hakim di Indonesia dalam putusannya terkait penjatuhan hukuman pidana terhadap pelaku IUUF di ZEE Indonesia. Mereka sepakat untuk menjatuhkan pidana denda, namun berbeda pendapat terkait penjatuhan pidana kurungan pengganti denda. Penelitian ini bertujuan untuk memahami alasan perbedaaan pandangan oleh hakim terhadap penerapan ketentuan-ketentuan dalam United Nations Convention on The Law of the Sea Tahun 1982 (UNCLOS 1982) dan memberikan rekomendasi optimasi penegakan hukum di bidang perikanan. Penelitian ini merupakan penelitian legal normatif dengan menggunakan data sekunder. Hasil penelitian menunjukkanbahwa perbedaan pandangan hakim berkaitan dengan pandangan mereka terhadap penerapan hukum internasional ke dalam hukum nasional, dan penting bagi Indonesia untuk memilih dan melakukan optimasi terhadap satu legal policy untuk menciptakan rezim penegakan hukum yang efektif.